Policy as normative influence? On the relationship between parental leave policy and social norms in gender division of childcare across 48 countries - Schindler, S.; Lindqvist, A.; Martiny, S.E. (British Journal of Social Psychology, 2024)
In the present work, we addressed the relationship between parental leave policies and social norms. Using a pre-registered, cross-national approach, we examined the relationship between parental leave policies and the perception of social norms for the gender division of childcare. In this study, 19,259 students (11,924 women) from 48 countries indicated the degree to which they believe childcare is (descriptive norm) and should be (prescriptive norm) equally divided among mothers and fathers. Policies were primarily operationalized as the existence of parental leave options in the respective country. The descriptive and prescriptive norms of equal division of childcare were stronger when parental leave was available in a country – also when controlling for potential confounding variables. Moreover, analyses of time since policy change suggested that policy change may initially affect prescriptive norms and then descriptive norms at a later point. However, due to the cross-sectional nature of the data, drawing causal inferences is difficult. © 2024 British Psychological Society.
Keywords: childcare; gender inequality; parental leave; policy; social norms; article; child care; cross-sectional study; diagnosis; epidemiology; father; female; gender; human; male; social norm